ChemInform Abstract: Iodine—Iodine Bonding Makes Tetra(diiodine)chloride, [Cl(I2)4]‐, Planar. Issue 9 (4th March 2014) - Walbaum, Christine; Richter, Mark; Sachs, Ulf; Pantenburg, Ingo; Riedel, Sebastian; Mudring, Anja‐Verena; Meyer, Gerd
Abstract Reaction of YI3 with bzc (bzc: benzo‐15‐crown‐5), NaCl, and iodine in MeOH lead to the formation of dark red to black plates of [(H5O2)(I2bzc)2] [Cl(I2)4] (I) and yellow needles or plates of [(H5O2)(I2bzc)2] [ICl2](I2bzc)2 (II).